Investigating the potential of energy flexibility in an office building with façade BIPV and a PV parking system - Santos, Miguel Freire David Dos (2017)
Building Integrated Photovoltaic (BIPV), is becoming an attractive solution in the context of high penetration of photovoltaic systems in buildings caused by the strive to achieve net or nearly zero energy status. Besides retrieving solar radiation to produce electrical energy, BIPV also offers aesthetical advantages because of its architectural feature. However, when integrated into vertical façades, the angle of the Photovoltaic (PV) modules may considerably affect the efficiency of BIPV when compared with horizontally oriented modules in the same location and latitude. This work reports on the electric energy performance of an office building, Solar XXI, located in Lisbon, Portugal, based on the opportunity of having two PV technologies in the same building. The system installed on the south façade is a BIPV (12 kWp) and the second is a parking lot PV installed in a nearby car park facility (12 kWp). This situation enables the comparison of Load Match Factors, but mainly Load Match Index, between the two systems. The use of small scale loads in energy flexibility operational measures to study the potential for flexible demand on an Net-Zero Energy Building (NZEB) office building is also possible. Two different scenarios were taken into development, from monitoring data obtained during March 2016 (winter period) and July 2016 (summer period). PVGIS is a tool used to verify the possibility of a PV optimization in the parking lot PV and EnergyPlus is used to create an energy consumption model of the building aiming to be validated by the real values.